Hadith #2591 - Sunan Abi Dawud - Ammar bin Mua'wiya bin Aslam al-Dahni عمار بن معاوية الدهني; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Sharayk bin 'Abdullah شريك بن عبد الله النخعي; Yahya bin Aadm bin Sulaiman يحيى بن آدم بن سليمان (Sunan Abi Dawud)
Yunus ibn Ubayd, client of Muhammad ibn al-Qasim, said that Muhammad ibn al-Qasim sent to al-Bara’ ibn Azib to ask him about the standard of the Messenger of Allah (ﷺ). He said: It was black and square, being made of a woollen rug.
Grade: Sahih

Hadith #2675 - Sunan Abi Dawud - Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Muhammad bin Shu'aib bin Shabur محمد بن شعيب بن شابور; Wathla bin al-'Asqa' (Sunan Abi Dawud)
We were with the Messenger of Allah (ﷺ) during a journey. He went to ease himself. We saw a bird with her two young ones and we captured her young ones. The bird came and began to spread its wings. The Messenger of Allah (ﷺ) came and said: Who grieved this for its young ones? Return its young ones to it. He also saw an ant village that we had burnt. He asked: Who has burnt this? We replied: We. He said: It is not proper to punish with fire except the Lord of fire.
Grade: Sahih

Hadith #2827 - Sunan Abi Dawud - Atab bin Bashayr عتاب بن بشير; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Muhammad bin Yahya bin Hiban محمد بن يحيى بن حبان (Sunan Abi Dawud)
I asked the Messenger of Allah (ﷺ) about the embryo. He replied: Eat it if you wish. Musaddad’s version says: we said: Messenger of Allah, we slaughter a she-camel, a cow and a sheep, and we find an embryo in its womb. Shall we throw it away or eat it? He replied: Eat it if you wish for the slaughter of its mother serves its slaughter.
Grade: Sahih

Hadith #4461 - Sunan Abi Dawud - Abdur-Razzaq عبد الرزاق بن همام; Ibn Jurayj ابن جريج; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Sa'id bin Jubayr سعيد بن جبير الأسدي (Sunan Abi Dawud)
A similar tradition (to the No. 4445) has also been transmitted by Salamah ibn al-Muhabbaq from the Prophet (ﷺ). This version has: If she asked her to have intercourse with her voluntarily, then she and a similar slave-girl would be given to her mistress from his property.
Grade: Hasan

Hadith #4841 - Sunan Abi Dawud - Abdullah bin Hmran عبد الله بن حمران; Abu Knanah al-Quraishi أبو كنانة القرشي; Abu Musa al-Asha'ari; Awf bin Abi Jamila al-A'rabi عوف بن أبي جميلة الأعرابي; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Ziyad bin Mkhraq زياد بن مخراق (Sunan Abi Dawud)
The Prophet (ﷺ) said: Every sermon which does not contain a tashahhud is like a hand cut off.
Grade: Sahih

Hadith #5077 - Sunan Abi Dawud - Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Muhammad bin Shu'aib bin Shabur محمد بن شعيب بن شابور; Muslim bin al-Harith (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: If anyone says in the morning: “There is no god but Allah alone Who has no partner; to Him belong the dominions, to Him praise is due, and He is Omnipotent,” he will have a reward equivalent to that for setting free a slave from among the descendants of Isma’il. He will have ten good deeds recorded for him, ten evil deeds deducted from him, he will be advanced ten degrees, and will be guarded from the Devil till the evening. If he says them in the evening
Grade: Sahih